RANCANGAN SISTEM INFORMASI ANEMIA PADA PLATFORM ONLINE “SRIKANDI HEALTH” BERBASIS PROGRESSIVE WEB APPS - Puji Handayani Putri (Poltekkes Kemenkes Padang, 2021)
Anemia is one of the nutritional problems that has the potential to hinder the development of the quality of Indonesian human resources. The support of science and information technology in the form of a website application can be a solution to facilitate education, monitoring and management of anemia so as to accelerate the handling of anemia. This study aims to design an anemia information system in the form of an online platform with the name